Angiotensin-I-Converting Enzyme Inhibitory (ACE-I) Peptide from Germinated Lamtoro Gung (Leucaena leucocephala ssp. glabrata (Rose) S. Zarate) Flour - Fitriani, Aprilia; Indrati, Retno; Marsono, Yustinus; Supriyadi, Supriyadi (Universitas Kebangsaan Malaysia, 2022)
Hypertension is a significant public health problem worldwide, a leading risk factor for cardiovascular disease and cause of premature death. Angiotensin-I-converting enzyme (ACE) activity is one of the causes of hypertension. Lamtoro Gung has potential as an Angiotensin-I-converting Enzyme Inhibitory (ACE-I) due to the presence of peptide that able to inhibit its activity to prevent hypertension. The germination process was carried out to hydrolyse storage proteins and produce peptides that have a low molecular weight. This study investigated ACE-I activity from Lamtoro Gung seed during germination and evaluated the blanching effect on it. This experiment was conducted with a Completely Randomised Design (CRD), and the factor is the differences in germination duration (0, 12, 24, 36, 48, 60, and 72 h). Proteolytic activity and the degree of hydrolysis during germination were studied to know the correlation between germination and ACE-I activity. The highest ACE-I activity sample was blanched with three different durations (2, 4, and 6 s). The 48 h germinated Lamtoro Gung had the highest ACE-I activity (70.62%). This result was supported by the proteolytic activity (168.79 U/g protein dry matter) and degree of hydrolysis (23.26%). Forty-eight hours of germination of Lamtoro Gung resulted in the highest ACE-I activity. Blanching of germinated Lamtoro Gung for 2 s could hold the ACE-I activity, but the longer duration decreased it.